Digital divides in education. An analysis of the Romanian public discourse on distance and online education during the COVID-19 pandemic - Alexandra Hosszu; Cosima Rughiniș (Sociologie Românească, 2020)
Adapting “face-to-face” education to distance/remote and/or online education in response to the COVID-19 pandemic has been a massive challenge for countries around the world. Online education reignited older debates about inclusive education, such as hoped-for universal access versus current digital divides, prompting the public to reflect about the past, the present, and future of the educational system. This article analyzes the Romanian public discourse, both scientific and non-scientific, on emerging distance and online education in Romania during the COVID-19 pandemic, in order to understand how public communication functioned as feedback for school digitalization. The paper charts the advantages and challenges of distance and online education experienced by various actors (teachers, students, and the members of civil society) or identified through scientific research, focusing on the way online education has spotlighted and reshaped social inequalities. We use thematic content analysis of 152 online articles published from March to June 2020 and eight scientific studies and reports. The results showed that public discourse about distance and online education was largely consistent within and across multiple stakeholders; also, the scientific reports were aligned with the other public opinions expressed and promoted via online channels. The general perspective of the emerging online education during COVID-19 is that it deepens the educational gaps and creates new forms of exclusion. On the positive side, some of the teachers have improved their teaching methods and educational content.